Editorial: Memory – Humanities and Social Sciences Contexts - Sieradzka-Baziur, Bożena (Horyzonty Wychowania, 2017)
Memory  is one of the essential concepts of science and it is presents in scientific works of psychology, pedagogy, sociology, linguistics, history, cultural studies, and also i.e. neurobiology or computer science...